Evaluation of Wall Material Admixture Threshold Values in Burning Zones of Fusion Devices - Seksembayev, Zhandos (The 6th International Conference on Nanomaterials and Advanced Energy Storage Systems. Institute of Batteries LLP, Nazarbayev University, and PI “National Laboratory Astana”., 2018)
One of the problems of fusion devices is wall material right selection that depends on the research purposes. In various fusion devices the admixture of wall or shell material could present in fuel mixture affecting the burning nature. The electronic component of admixture creates additional radiation losses, then use of low Z material allows reducing them, however ionic component could be involved in producing energy. Both loss and gain depend on the temperature value. Also one should consider tolerance to high temperature. In this work we try to evaluate an admixture’s approximate threshold value that still could allow to keep the burning efficient at extreme conditions in traditional reactors as well as in specific ones for different fusion fuel types. It is obtained that the most capable fuel type DT allow up to several dozens percent of admixture in fuels concentration to be present at extreme conditions. The obtained values will be useful upon selection of suitable wall material.